2015
DOI: 10.1016/j.lwt.2014.09.037
|View full text |Cite
|
Sign up to set email alerts
|

Novel mango bars using gellan gum as gelling agent: Rheological and microstructural studies

Abstract: a b s t r a c tThis work aimed the development of mango bars, made with fresh mango puree and gellan gum. The influence of gellan concentration as well as the ratio of LA (low-acyl) and HA (high-acyl) gellan on the rheological and microstructural properties of the mango bars was studied. Rheological outcomes showed that both LA and HA, and in mixtures, were able to produce jellified products, within a rather low maturation time. Furthermore, a synergistic effect was observed at different ratios of LA/HA, enabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 42 publications
1
21
0
Order By: Relevance
“…Danalache et al (2015a) analyzed mango bars solid texture with different concentrations of gellan gum (high and low acyl) and found that low concentrations of gellan (0.75% high acyl and 0.25% low acyl) provided the desired texture, corroborating with the present study. On another study, Danalache et al (2015b) verified the rheological characteristics of mangos, the kinetics of forming gels, and concluded that the high percentage of gellan gum (high acyl) and sucrose tends to compromise the quality of the gel, weakening it.…”
Section: Sensory Acceptance Of Fruit Pastementioning
confidence: 93%
See 1 more Smart Citation
“…Danalache et al (2015a) analyzed mango bars solid texture with different concentrations of gellan gum (high and low acyl) and found that low concentrations of gellan (0.75% high acyl and 0.25% low acyl) provided the desired texture, corroborating with the present study. On another study, Danalache et al (2015b) verified the rheological characteristics of mangos, the kinetics of forming gels, and concluded that the high percentage of gellan gum (high acyl) and sucrose tends to compromise the quality of the gel, weakening it.…”
Section: Sensory Acceptance Of Fruit Pastementioning
confidence: 93%
“…properties that confer such taste (Canuto et al, 2010;Carvalho et al, 2015;Gadelha et al, 2009). This high acidity is responsible for influencing the structure of the gel, thus promoting syneresis (Danalache et al, 2015b).…”
Section: Cata Test Analysismentioning
confidence: 99%
“…Gellan is a food gum off-white powder that is primarily used as a gelling or thickening agent. It is approved as a food additive and widely used in confectioneries, jams, jellies, fabricated foods, hydrogels, pie fillings, puddings, ice cream and yogurt (Danalache et al, 2014).…”
Section: Gellan Gummentioning
confidence: 99%
“…Gellan and its products can also be applied in the fields of food, medicine and chemical industry [3]. In order to investigate the mechanism of gellan lyase and to produce gellan oligosaccharide, would be one of the more effective ways to expand its application value [4]. Therefore, we chose to use efficient gellan lyase to improve its molecular structure and expand its application range.…”
Section: Introductionmentioning
confidence: 99%